Structural analysis of three pivotal SERK dependent PRR complexes of Arabidopsis thaliana - Alvy, Raghib Ishraq (Brac University, 2021)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Master of Science in Biotechnology, 2021.